The concept of a closed resource cycle using an innovative information system for the development of bioenergy - A. A. Aristova; O. V. Novikova (Известия высших учебных заведений: Проблемы энергетики)
RELEVANCE. The impossibility of using existing information systems, such as territorial waste management schemes (TSOs) to form a balance of supply and demand. TSOs do not allow us to identify the volume of demand and supply for processing technologies, and equipment manufacturers are not focused on understanding the balance of demand across the country. Technological development in terms of creating new facilities for energy waste processing requires justification of prospects for investment.THE PURPOSE. Develop the concept of a closed resource cycle using information flows aimed at identifying participants in the process. The desired tool should provide an understanding of the need for the production of bioenergy equipment, the potential for demand for R&D, as well as the formation of state programs to support the creation of enterprises for the processing of municipal solid waste (MSW) and the production of bioenergy equipment.METHODS. The development of the concept of a closed resource cycle is characterized by the design of the concept, which includes the methods of divergence, transformation, and convergence.RESULTS. The paper describes the relevance of the topic associated with the impossibility of using existing information systems such as territorial waste management schemes (TSMS) to form a balance of supply and demand for processing technologies. Potential participants in the formation of a closed resource cycle throughout the life cycle of a waste processing project are identified, with the role of participants and the links between them, as well as the characteristics of the information flow of each participant, identified. A concept is proposed based on the formation of an information system in which each participant can maximize their needs for resources and effect.CONCLUSION. The proposed system makes it possible to improve the existing waste management system, ensures the return of generated waste to the resource cycle. systems - the balance of generated and recycled waste. The main difference between the proposed system and the federal state information system for accounting and control of waste management of classes I and II is the principle of operation - the system is based on the source of waste generation, ensuring the balance of generating and processed waste.